What Factors Lead Companies to Adopt Social Media in their processes: Proposal and Test of a Measurement Model - Jozé Braz de Araújo; Silvia Novaes Zilber (BBR: Brazilian Business Review)
The objective of this study was to understand which factors lead companies to use social media to achieve results. For that, a theoretical model was proposed and tested. Data was collected using a survey of 237 companies. In the analysis we analysis used the structural eq uation modeling technique. The results show that the social media relative advantage and its observability were important factors to social media organizational adoption. We also found that big companies with more formalized organizational structure (OS) t end to adopt social media more than small ones with no formal OS. The companies studied showed strong organizational disposition for innovation adoption.